Transforming Population Administration for Global Smart Cities through Sipraja - Agustina, Nuke Kenya; UB, Ahmad Riyadh (Universitas Muhammadiyah Sidoarjo, 2024)
This study analyzes the implementation of the SIPRAJA Application Program for population administration services in Bluru Kidul Village. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation, and analyzed using Miles and Huberman's model. The study, guided by Merille S. Grindle's framework, found that while SIPRAJA aligns with its objectives and provides timely service satisfaction, it faces challenges in socialization and technological readiness. Only 19% of residents use the program, preferring conventional services due to technological limitations and unavailable system features. The findings highlight the need for improved socialization and training to enhance resident participation and system effectiveness, contributing to smart city goals. Highlights: Program Success: SIPRAJA meets objectives, offers timely service satisfaction. Challenges: Socialization and technological readiness limit resident participation. Recommendations: Improve socialization and training for better system adoption. Keywords: SIPRAJA, population administration, Bluru Kidul, qualitative research, public service